Adhesivity of bio-based anhydrous citric acid, tannin-citric acid and ricinoleic acid in the properties of formaldehyde-free medium density particleboard (MDP) : Mogućnost primjene ekološki prihvatljivoga anhidrida limunske kiseline, taninskolimunske kiseline i ricinoleinske kiseline kao ljepila za proizvodnju iverica srednje gustoće (MDP) bez formaldehida - Teixeira, Divinio Eterno (Array, 2020)
Particles of flooded gum (Eucalyptus grandis) were bonded using three bio-based adhesives - anhydrous citric acid (CA), tannin-citric acid (TCA) and ricinoleic acid (RA) - from renewable sources and hot pressed to produce medium density particleboard (MDP). The bonding capacity of such adhesives and properties of the MDP were evaluated and compared to the requirements of seven grades of particleboards, according to the EN 312 (2010) standard. The RA did not create adhesion reaction with the wood particles. Adhesives formulated with CA and TCA presented capacity to bond eucalyptus particles into MDP confirmed by esterification reactions of the FTIRS analysis. MDP bonded with CA met requirements as high as grade P5 of the EN 312 (2010) standard for static modulus of elasticity (MOE) and internal bond (IB) and P2 for modulus of rupture (MOR). Panels bonded with TCA met requirements up to grade P3 for MOE, however, did not withstand water absorption.